Screening for marginal food security in young children in primary care - Imaan Bayoumi; Catherine S. Birken; Kimberly M. Nurse; Patricia C. Parkin; Jonathon L. Maguire; Colin Macarthur; Janis A. Randall Simpson; Cornelia M. Borkhoff (BMC, 2021)
Abstract Background Household food insecurity (FI), even at marginal levels, is associated with poor child health outcomes. The Nutrition Screening Tool for Every Preschooler (NutriSTEP®) is a valid and reliable 17-item parent-completed measure of nutrition risk and includes a single item addressing FI which may be a useful child-specific screening tool. We evaluated the diagnostic test properties of the single NutriSTEP® FI question using the 2-item Hunger Vital Sign™ as the criterion measure in a primary care population of healthy children ages 18 months to 5 years. Results The sample included 1174 families, 53 (4.5%) of which were marginally food secure. An affirmative response to the single NutriSTEP® question "I have difficulty buying food I want to feed my child because food is expensive" had a sensitivity of 85% and specificity of 91% and demonstrated good construct validity when compared with the Hunger Vital Sign™. Conclusion The single NutriSTEP® question may be an effective screening tool in clinical practice to identify marginal food security in families with young children and to link families with community-based services or financial assistance programs including tax benefits. Trial registration TARGet Kids! practice-based research network (Registered June 5, 2013 at www.clinicaltrials.gov ; NCT01869530); www.targetkids.ca